2003
DOI: 10.1523/jneurosci.23-05-01557.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Wake-Promoting Hypocretin–Orexin Neurons Are in an Intrinsic State of Membrane Depolarization

Abstract: Wakefulness depends on the activity of hypocretin-orexin neurons because their lesion results in narcolepsy. How these neurons maintain their activity to promote wakefulness is not known. Here, by recording for the first time from hypocretin-orexin neurons and comparing their properties with those of neurons expressing melanin-concentrating hormone, we show that hypocretin-orexin neurons are in an intrinsic state of membrane depolarization that promotes their spontaneous activity. We propose that wakefulness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
142
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(155 citation statements)
references
References 41 publications
12
142
1
Order By: Relevance
“…The outward shift of resting currents on replacing Na ϩ with NMDG ϩ is consistent with a resting sodium conductance (with TTX present), similar to previous results in deep cerebellar nuclear cells (Raman et al, 2000) and orexinergic neurons (Eggermann et al, 2003). The outward shift of currents after Na ϩ removal could also represent enhancement of an outward Na/K ATPase electrogenic pump current (owing to reduction of the sodium gradient) or elimination of Na/Ca exchanger current.…”
Section: Resting Potential and Background Conductancesupporting
confidence: 88%
“…The outward shift of resting currents on replacing Na ϩ with NMDG ϩ is consistent with a resting sodium conductance (with TTX present), similar to previous results in deep cerebellar nuclear cells (Raman et al, 2000) and orexinergic neurons (Eggermann et al, 2003). The outward shift of currents after Na ϩ removal could also represent enhancement of an outward Na/K ATPase electrogenic pump current (owing to reduction of the sodium gradient) or elimination of Na/Ca exchanger current.…”
Section: Resting Potential and Background Conductancesupporting
confidence: 88%
“…We find a similar fraction of PF LH neurons to be MCH positive by single-cell PCR analysis (Pakkanen et al, 2005). Previous reports from other laboratories have associated the bipolar morphology and tonic firing rate profile as seen in our type 3 neurons with orexin-expressing cells in LH slices (Li et al, 2002;Eggermann et al, 2003;Gao et al, 2003). Also, van den Pol and colleagues demonstrated that MCHpositive neurons in culture, as well as in brain slice preparations, show spikefrequency adaptation with sustained depolarization and responses to hyperpolarizing current that are similar to that of our type 1 neurons (Gao et al, 2003;van den Pol et al, 2004).…”
Section: Basic Characteristics Of Lh Neurons Studiedsupporting
confidence: 83%
“…These differences in membrane potential response to depolarization indicate differences in the expression of depolarization-activated ion channels. For example, postinhibitory hyperpolarization of orexin cells is likely to be caused by A-type K ϩ channels (21), while postinhibitory excitation could theoretically be due to I CAN channels present in orexin cells (25). However, our voltageclamp analysis (Fig.…”
Section: Discussionmentioning
confidence: 94%